Evaluation of The Block System Implementation at Permata Harapan Vocational High School - Ilmi, Miftahul; Rukun, Kasman; Miftahul Ilmi (LPPM Undiksha, 2020)
This study aimed to evaluate the block system implementation in Permata Harapan Vocational High School based on (1) understanding and apply the block system conducted by teaching staff, (2) understanding of block system implementation by students, (3) availability of facilities and infrastructure at Permata Harapan Vocational High School to support good student competence. This research was a descriptive study. Data was collected by using a questionnaire method based on the CIPP evaluation model (context, input, process, product). The subjects of this study were 50 students in grade X and XI Permata Harapan School and several officials high school. The description of the data carried out by considering the frequency distribution and determining the Level of Respondent Achievement (TPR) in each component and indicator which compared with the criteria. The results showed that the scores were based on an understanding of the implementation of the block system using the CIPP evaluation method which included in moderate category and reached 68.65% percent, with details of each aspect: (1) the context aspect was 81.94%, (2) 63.89% of input aspects, (3) 67.70% of process aspects, (4) 71.52% of product aspects. Based on the discussion results of observation and documentation, the average achievement of all aspects was 82.47%. So, the implementation of the block system at SMK Permata Harapan has been in good classification but it still needs improvement in various aspects so that the goal of implementing the block system can be achieved perfectly.